If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(-13 + a) = 0 (-13 * a + a * a) = 0 (-13a + a2) = 0 Solving -13a + a2 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), 'a'. a(-13 + a) = 0Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(-13 + a)' equal to zero and attempt to solve: Simplifying -13 + a = 0 Solving -13 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + a = 0 + 13 Combine like terms: -13 + 13 = 0 0 + a = 0 + 13 a = 0 + 13 Combine like terms: 0 + 13 = 13 a = 13 Simplifying a = 13Solution
a = {0, 13}
| n(8-n)=0 | | 0.18x=3500-x | | x-7x-60=0 | | f(-4)=4x+5 | | 21^(1/6)/1029^(1/5) | | 2(x+8)=3(x-8) | | 6(x+6)-8=0 | | 49-x^2/21x^3 | | 7-x/3x^5 | | x+12x-45=0 | | 4r-4/r-2 | | 1/5(01 | | 0.4y=5y | | 4(w-7)-(-9w-1)=12w | | (3x+30)+x=90 | | f(x+6)=6x+-8 | | 7-8/6=7 | | -5(x+2)=5-(-1) | | 7e^2x=2 | | x+7x-30=0 | | 100(90+8)+2(90+8)= | | 15x-4=5x-54 | | 6x^2(8x+1)+8x+1= | | 0.62=log(x) | | 3(x+1)-4(x-2)= | | -3/13=9 | | f(x)=4(1.5) | | -7.2/0.6 | | -3/13=-0 | | 3/5:[4/5-3x(2-4/5)] | | 12+8=420 | | 7/15x-3/15=4 |